Modulador acusto-óptico en amplitud de fibra óptica basado en ondas acústicas de flexión - Bello-Jiménez, M.; Cuadrado-Laborde, C.; Díez, A.; L, J.; V, M. (Revista Mexicana de Física, 2014)
An experimental study of an in-fiber acousto-optic modulator (AOM) based on the acousto-optic interaction produced by standing flexural acoustic waves is reported. We focus our attention in the effects of a gradual reduction in the optical fiber as the mechanisms to improve the spectral response of the AOM. As a particular case we report a 70-μm fiber AOM. Our approach permits the implementation of high modulation depth (60%), low optical loss (1.3 dB) and a 3 dB broad modulation bandwidth of 40 nm, operating in the MHz frequency range. The experimental results demonstrate that including tapered optical fibers can be regarded as an extra degree of freedom to control the optical bandwidth of the modulator.